Experiences in Managing Hospital Accreditation, in Accordance with The International Standard of Nurse Administrators - Bunyasartphan, Duangduan; Chaiphibalsarisdi, Puangtip; Apiruknapanond, Panta (Journal of The Royal Thai Army Nurses, 2020)
The objective of this research was to describe the experiences in managing hospital accreditation in accordance with the international standard by nurse administrators. The Hermeneutic phenomenology of Heidegger was being applied as research methodology. Nine key informants of nurse administrators from those international standard accredited hospitals were being selected. Data collections were in-dept interviews by telephoning and tape recording. Verbatim transcription and analyzed with thematic extraction as proposed by Van Manen were performed. The study results had found nine themes as follows; 1) Policy on upgrading hospitals toward international standard. 2) Insure that the allotted budget is sufficient. 3) Sizable nursing team, all committee assigned. 4) Enhancing one’s knowledge, be closely with the experts. 5) All must be communicated, harmonized, united in action and spirit. 6) Be prepared, reviewed, rehearsed until the day of inspection. 7) Worthiness of outcomes leading to safety. 8). Continuous quality improvement emphasizing advancement and 9) Upgrade hospital but increasing burden on documents to nurses. Result of the research had revealed that experiences of nurse administrators in managing hospital accreditation in accordance with the international standard was as planned, the outcome was satisfied and must be proceeded on a continuing basis.